009.2 Establishment of the gonorrhoea mouse model for pre-clinical testing of antimicrobial agents against neisseria gonorrhoeae. (13th September 2015) - Connolly, KL; Hiltke, TJ; Gomez, C; Unemo, M; Jerse, AE
Abstract : Introduction: New antibiotics for gonorrhoea are needed due to the emergence of resistance to the extended-spectrum cephalosporins (ESCs) in Neisseria gonorrhoeae . Here we established the 17β-estradiol mouse model of gonococcal genital tract infection for testing antibiotics against gonorrhoea by defining the in vivo efficacy of cefixime (CFX) and ceftriaxone (CRO) against strain FA1090 (ESC S ) and the multi-drug resistant strain H041 (ESC R ). Methods: Estradiol-treated female BALB/c mice were inoculated vaginally with FA1090 or H041 bacteria. PBS or different doses of CFX or CRO were administered two days later (n = 9 mice/group) and vaginal swabs were quantitatively cultured for N. gonorrhoeae for 8 consecutive days. The percentage of mice colonised over time was compared among groups using the Log-rank test. Results: A single oral dose of 60, 12, 6 or 3 mg/kg CFX showed significant activity against strain FA1090 with the two highest doses clearing infection within 48 hr. One or two mice in the groups that received 6 or 3 mg/kg CFX did not clear infection. None of four higher concentrations (120, 60, 12, and 6 mg/kg) of CFX cleared H041 infection, but gentamycin (48 mg/kg, i.p. injection, 5 days, q24h) was effective compared to PBS. Five concentrations (30, 15, 5, 1.5, and 0.5 mg/kg) of a single i.p. dose of CRO had significant activity against FA1090, while 60, 30, 15, or 1.5 mg/kg had no effect against H041. Conclusion: The gonorrhoea mouse model shows a dose-dependent response for CRO and CFX against an ESC S strain with in vivo break-points less than 0.5 and 3 mg/kg, respectively. Higher doses of these antibiotics were not effective against an ESC R strain. We are currently correlating in vivo efficacy with pharmacokinetic analyses to further strengthen the usefulness of this model to test antimicrobial compounds against gonorrhoea. Disclosure of interest statement: This work was supported by NIH/NIAID (Interagency Agreement AAI14024–001) and USUHS (USU-DOD MIC73–2493).